Spelling Bee Competition untuk Meningkatkan English Literacy di TBM Karya Muda, Bojonegoro - Chyntia Heru Woro Prastiwi; Rika Pristian Fitri Astuti; Fifi Zuhriah; Meiga Ratih Tirtanawati; Ria Ristiana; Rhofiqoh Inayatin (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2025)
Community Reading Park or Taman Bacaan Masyarakat (TBM) is a non-formal educational facility that provides literacy and cultural services to the community. Although TBMs are established based on four legal foundations, in practice, several TBMs face both external and internal challenges. TBM Karya Muda, located in Klepek Village, Sukosewu District, Bojonegoro Regency, also faces both types of challenges. They include a low number of visitors, a limited book collection, lack of variety in TBM programs, limited availability of the management team, minimal funding, lack of collaboration, and unmotivated children visitors who prefer gadgets over reading. Considering the environmental potential of TBM, with 17 schools in its surrounding area, this condition became the basis for the PkM Team to conduct a Spelling Bee Competition at TBM Karya Muda, involving 30 elementary school children from grades 2 to 6. The activity aims to foster a culture of literacy—reading, writing, listening, and speaking—in English from an early age. Spelling ability is a foundational skill for reading and writing literacies. The Spelling Bee Competition was carried out in three stages: preparation, implementation, and closing. The results of the PkM activity show that the Spelling Bee Competition helped increase children's English vocabulary, improve memory, boost self-confidence, motivate healthy competition, and strengthen literacy in reading and writing.